2007
DOI: 10.5194/aab-50-240-2007
|View full text |Cite
|
Sign up to set email alerts
|

Milk production and reproduction traits of different grades of zebu x Friesian crossbreds under semi-arid conditions

Abstract: Data from Zebu x Friesian crossbred dairy cows of different upgrading kept in the Kenana Sugar Company (KSC) farm, 300 km south of Khartoum on the bank of the White Nile in the low rainfall savannah region were collected over a period from 1984 to 2004 and analyzed using Harvey's (1990) Least Squares programme. The results indicated that there were no significant differences in milk yield per lactation, daily milk yield and lactation between the 25% and 37.5% genetic groups. The 50% Zebu x Friesian group produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
4
10
1
Order By: Relevance
“…The mean value of 47 months of AFC found in this study for the crossbred cows is higher than the average value of 36 months reported by Emebet and Zeleke (2007) for crossbred cattle in Eastern lowlands and Shiferaw et al (2003) of 41 months in central highlands in Ethiopia and 35 months reported by Asimwe and Kifaro (2007) for F 1 's in Tanzania. On the other hand, our finding was comparable with the reports of Ahmed et al (2007) for 25% crossbreds in semi-arid regions of Sudan (46 months). The lower AFC observed in crossbred cows than indigenous ones in this study is in agreement with the reports of Negussie et al (1998) in Ethiopia and Nigongoni et al (2006) in Zimbabwe, but in contrast with the finding of Asimwe and Kifaro (2007) in Tanzania who reported that AFC increases with the level of exotic blood level.…”
Section: Discussionsupporting
confidence: 95%
“…The mean value of 47 months of AFC found in this study for the crossbred cows is higher than the average value of 36 months reported by Emebet and Zeleke (2007) for crossbred cattle in Eastern lowlands and Shiferaw et al (2003) of 41 months in central highlands in Ethiopia and 35 months reported by Asimwe and Kifaro (2007) for F 1 's in Tanzania. On the other hand, our finding was comparable with the reports of Ahmed et al (2007) for 25% crossbreds in semi-arid regions of Sudan (46 months). The lower AFC observed in crossbred cows than indigenous ones in this study is in agreement with the reports of Negussie et al (1998) in Ethiopia and Nigongoni et al (2006) in Zimbabwe, but in contrast with the finding of Asimwe and Kifaro (2007) in Tanzania who reported that AFC increases with the level of exotic blood level.…”
Section: Discussionsupporting
confidence: 95%
“…The higher milk yield was reported in cows calved in winter season; followed by rainy and summer seasons [9]. The results reported by Ahmad, et al and Baloch were also in agreements with the findings of current study for milk yield [6,17]. They also reported that the season of calving had a significant effect (P < 0.05) on milk yield.…”
Section: Effect Of Season On Milk Yieldsupporting
confidence: 90%
“…In contrast to the finding of current study the daily milk production was significantly higher (P < 0.01) in cows that calved in summer and autumn than those that calved in winter and spring [20]. Increase in production caused by maturation and increase in body weight [21,6]. The cows of the same age but different parity were variation in production [22,6].…”
Section: Effect Of Season On Milk Yieldmentioning
confidence: 73%
See 2 more Smart Citations